Peritonsillar abscess in an infant with congenital bone marrow failure. (September 2019) - Pericleous, Agamemnon; Wilkinson, Sophie; Gerrish, Amy; Daniel, Mat
Abstract: Peritonsillar abscess is extremely rare in infants and is potentially life-threatening. We report the case of a 3 month old infant with a background of congenital bone marrow failure who presented with sepsis and desaturation requiring intubation and PICU care. Ultrasound and CT scan revealed an inflammatory mass. Examination in theatre revealed a self-draining quinsy. Following formal drainage in theatre, the child improved and was extubated uneventfully 1 day later. Prompt surgical and medical management as well as the presence of a well-coordinated multidisciplinary team are crucial in ensuring the adequate management of complex paediatric patients.